Perancangan Buku “Jaje Pulegembal Payas” Sebagai Sarana Literasi Serati Banten Di Desa Sedang - I Putu Dudyk Arya Putra; Desak Putu Yogi Antari Tirta Yasa (Departement of Mathematics Education, 2023)
Yadnya is a sincere holy sacrifice that can be displayed in symbolic forms that are used as a means of worship and offerings to God. Symbols from nature can be seen in the content and form of presentation of ceremonial means. Banten is the main means of ceremony used to realize these offerings. Broadly speaking, ceremonies in Bali are divided into 3 levels, namely Nista, Madya and Utama. The means of ceremony in the form of offerings also differ depending on the level of the ceremony. Jaje pulogembal payas is one part of the banten. The basic ingredients of Pulegembal are made from rice flour which is processed using warm water, after which it is colored and kneaded until it resembles a dough which can then be shaped. After forming, jaje pulogembal payas is then fried and dried in the sun to preserve it before being used as a means of ceremony. In the past, this pulegembal dye used natural dyes, but in its development, food coloring has now been used. The forms of Jaje pulogembal payas are depictions of the universe and its contents, starting from humans, animals, trees, marine life, to the tools used in everyday life. Generally, the people who make jaje pulogembal payas are the Serati. Serati is a person who has expertise in making a series of ceremonial facilities at religious ceremonies in Bali and has been ordained in the form of a ceremony and whose existence is recognized by the village. In addition, the opportunity to learn how to make jaje pulogembal payas is only there when there is a big ceremony at the intermediate or primary level, so jaje pulogembal payas is not made all the time. This rare learning opportunity, coupled with the sometimes stiff properties of Serati, makes jaje pulogembal payasini have a 'tense' impression that not everyone has the courage to learn it. Therefore, especially literacy tools that can display jaje pulogembal payas visually are very important in preserving the knowledge of making jaje pulegembal. Medium Village was chosen as the location of the case object because Medium Village is the village of the writer, so the writer has close proximity to the location so that the writer really understands the situation and conditions in the field. This study uses qualitative research methods with observation, interviews, visual materials and documentation.